TEKNIK BUDIDAYA DAN PENGOLAHAN TERIPANG PASIR (Holothuria scabra) BAGI PEMUDA GEREJA RANTING I BAITRAFA, NEGERI SULI KECAMATAN SALAHUTU, KABUPATEN MALUKU TENGAH - D. Manuputty, Gratia; M. Pattinasarany, Maureen; V. Limmon, Gino; A. Noya, Yunita (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
Sandfish cultivation is a meaningful way that is necessary to fulfil the production, and learning the processing aspect is also crucial to achieve a better price in selling. Suli, a coastal area, has a high potency of sandfish that needs management; however, the knowledge and skill of Suli’s people are still low regarding sandfish culture and processing. The community service program was conducted through the socialization of cultivation concept, training of sandfish processing technique, and evaluation to measure the program’s effectiveness in enhancing people’s knowledge and skill. The evaluation results indicate an increase in knowledge and skills, both for the concept of cultivation and processing techniques. The percentage of target recognition for the organisms is relatively high (83.33%), as sandfish is generally found in Suli intertidal, yet, the common name and scientific name of sandfish are not cognizant. The low percentage is more related to cultivation (12.50-16.67%) due to marine culture being infrequent in Suli waters, whereas the processing has a higher percentage (41.67%). The knowledge and skill of people are increasing after the program. Furthermore, the support of the local government is needed to stimulate the youth in the cultivation and processing business of sandfish so that the level of unemployment will decrease